Tracing children's vocabulary development from preschool through the school‐age years: an 8‐year longitudinal study. Issue 1 (24th June 2014) - Song, Shuang; Su, Mengmeng; Kang, Cuiping; Liu, Hongyun; Zhang, Yuping; McBride‐Chang, Catherine; Tardif, Twila; Li, Hong; Liang, Weilan; Zhang, Zhixiang; Shu, Hua
Abstract In this 8‐year longitudinal study, we traced the vocabulary growth of Chinese children, explored potential precursors of vocabulary knowledge, and investigated how vocabulary growth predicted future reading skills. Two hundred and sixty‐four (264) native Chinese children from Beijing were measured on a variety of reading and language tasks over 8 years. Between the ages of 4 to 10 years, they were administered tasks of vocabulary and related cognitive skills. At age 11, comprehensive reading skills, including character recognition, reading fluency, and reading comprehension were examined. Individual differences in vocabulary developmental profiles were estimated using the intercept‐slope cluster method. Vocabulary development was then examined in relation to later reading outcomes. Three subgroups of lexical growth were classified, namely high‐high (with a large initial vocabulary size and a fast growth rate), low‐high (with a small initial vocabulary size and a fast growth rate) and low‐low (with a small initial vocabulary size and a slow growth rate) groups. Low‐high and low‐low groups were distinguishable mostly through phonological skills, morphological skills and other reading‐related cognitive skills. Childhood vocabulary development (using intercept and slope) explained subsequent reading skills. Findings suggest that language‐related and reading‐related cognitive skills differ among groups with different developmental trajectories of vocabulary, and the initial size and growth rate of vocabulary may be two predictors for later reading development.